HIGHLIGHTING STUDENTS’ LEARNING STYLES TOWARD THE ENGLISH INSTRUCTION IN EFL CONTEXT (Jurnal Bahasa Lingua Scientia, 2024)
This study aims at identifying students’ learning styles in learning as a foreign language. The participants involve 26 students of English education program. To collect the data, questionnaires are employed. The findings show 46% of students include using kinesthetic learning styles for learning. These students preferred to learn through practical application of knowledge or some kind of related activity and 0% of the 26 students who reached a level of about 6.5% chose to learn to read and write. Despite this, the learning achievement of students with kinesthetic learning styles is higher compared to visual, auditory and reading and writing learning styles. Another result of the study was that English education students did not like the learning style of reading and writing. The students are suggested to have the intention toward initiatives and motivation in the learning process in determining the learning styles they engaged.
Keywords: EFL students; learning style; English instruction